NIGERIA’S GROWTH CHALLENGES: A CRITICAL RE-EXAMINATION OF THE BRITISH COLONIAL RULE - Jacob, Uche Henry; Amiara, Amiara Solomon; Nwigwe, Nneka Rose (EBSU Journal of Social Sciences and Humanities, 2024)
Nigeria’s growth challenges are rooted in the economic exploitations and social distortion orchestrated by the British colonial administration in the 19th century. Over the years, scholars in the field of Political Science, History and International Relations have emphasized much on the impacts of colonialism with less reference to how the British colonial legacies are continuing to deepen the underdevelopment crisis in Nigeria. This paper seeks to highlight some of the British colonial antecedents that are currently hampering Nigeria’s growth and development. A critique of British sinister activities during and after colonialism is offered here to foster new discussion that will provoke a rethink of the approaches to the growth challenges. Also, the paper adds that, while international cooperations are necessary for growth, however, Nigeria requires indigenous solutions that are carefully crafted to deal with the overdependence issues that are crippling the economy. It argues that although slave trade, colonialism, neo-colonialism and internal problems such as corruption among other factors contributed to the underdevelopment in Nigeria, nevertheless, it is the lack of innovative ideas and inability of successive regimes to articulate national development plans and strictly follow them that acerbated the growth crisis. The paper concludes that the British imperial activities are still impacting negatively on Nigeria as well as influencing the behavior of leaders who adopted many of the colonial legacies. Data was collected using the qualitative approach, relying majorly on secondary and primary sources. Secondary materials were drawn from books and journal articles, while the primary sources came from official memos, videos, archival documents, pictures etc. Analyses were anchored on thematic technique, which is in sync with the Theory of Imperialism used to explain the underdevelopment challenges in Nigeria.